The Role of Religion and Spirituality in Mindfulness Practices: A Qualitative Literature Review - María Teresa Gargiulo (SMARATUNGGA: JURNAL OF EDUCATION AND BUDDHIST STUDIES, 2023)
In recent decades, the academic literature on mindfulness has grown rapidly as it uncovers similarities and differences between mindfulness practices in Buddhism, Stoic philosophy, and Christian meditation. This research, which is still in its early stages, aims to distinguish the specific notes or elements that represent each of these mindfulness practices within a conceptual framework. Measuring mindfulness practices' efficiency and therapeutic efficacy requires selecting a subset of variables that specifically represent the practice. Failure to do so may result in a threat to construct validity. This qualitative study aims to explore the relationship between mindfulness and spirituality by collecting data through a literature review. The results reveal that religion, ethics, and spirituality are crucial components of the explanatory model of mindfulness practice. This is because religious and spiritual traditions allow it to become a form of psychotherapy with various modalities of attention regulation. This study contributes to the scientific understanding of mindfulness practices by highlighting the importance of examining them in the context of religion and spirituality and developing a better conceptual understanding of them across different traditions.